Making ecological indicators management ready: Assessing the specificity, sensitivity, and threshold response of ecological indicators. (October 2019) - Fu, Caihong; Xu, Yi; Bundy, Alida; Grüss, Arnaud; Coll, Marta; Heymans, Johanna J.; Fulton, Elizabeth A.; Shannon, Lynne; Halouani, Ghassen; Velez, Laure; Akoglu, Ekin; Lynam, Christopher P.; et al.
Highlights: Gradient forests were used to assess the performance of 14 ecological indicators. Indicators' responses to fishing and environment were compared across 10 ecosystems. High specificity to fishing was found for most indicators in seven of 10 ecosystems. Biomass to fisheries catch ratio was most sensitive to low level of fishing pressure. Aggregated biomasses were more sensitive to environmental change than to fishing. Abstract: Moving toward ecosystem-based fisheries management (EBFM) necessitates a suite of ecological indicators that are responsive to fishing pressure, capable of tracking changes in the state of marine ecosystems, and related to management objectives. In this study, we employed the gradient forest method to assess the performance of 14 key ecological indicators in terms of specificity, sensitivity and the detection of thresholds for EBFM across ten marine ecosystems using four modelling frameworks (Ecopath with Ecosim, OSMOSE, Atlantis, and a multi-species size-spectrum model). Across seven of the ten ecosystems, high specificity to fishing pressure was found for most of the 14 indicators. The indicators biomass to fisheries catch ratio (B/C), mean lifespan and trophic level of fish community were found to have wide utility for evaluating fishing impacts. The biomass indicators, which have been identified as Essential Ocean Variables by the Global Ocean Observing System (GOOS), had lower performance for evaluating fishing impacts, yet they were most sensitive to changes in primary productivity. The indicator B/C was most sensitive to low levels of fishing pressure with a generally consistent threshold response around 0.4* F MSY (fishing mortality rate at maximum sustainable yield) across nine of the ten ecosystems. Over 50% of the 14 indicators had threshold responses at, or below ∼0.6* F MSY for most ecosystems, indicating that these ecosystems would have already crossed a threshold for most indicators when fished at F MSY . This research provides useful insights on the performance of indicators, which contribute to facilitating the worldwide move toward EBFM.